Effects of treatment time by sulphur hexafluoride (SF 6) plasma on barrier and mechanical properties of paperboard - Jinkarn T. (2014)
Sulphur hexafluoride (SF 6) plasma, using inductively coupled plasma technique, was applied on paperboard surfaces. Effects of different treatment times on water and oil resistances, mechanical properties (through tensile, compression and folding endurance tests) and barrier properties [through water vapor transmission rate (WVTR) and oxygen transmission rate (OTR)] were determined. Results showed that SF 6 plasma treatment can improve water resistance properties of paperboard significantly, beginning with only a 2 s treatment time (p ≤0.05), whereas oil resistance properties can be improved over a longer time period. Plasma treatment had no effect on tensile strength of treated paperboard; however, machine direction (MD) compression strength, as well as MD and CD folding endurance, of treated paperboard was significantly lower than that for an untreated sample (pa≤ 0.05). WVTR and OTR of treated paperboard were higher with increasing treatment time, because of fluorine atoms and electron bombardment causing etching of cellulose fibres. © 2011 John Wiley & Sons, Ltd.